Interactions between a phenolic antioxidant, moisture, peroxide and crosslinking by-products with metal oxide nanoparticles in branched polyethylene. (March 2016) - Liu, D.; Pourrahimi, A.M.; Pallon, L.K.H.; Sánchez, C. Cobo; Olsson, R.T.; Hedenqvist, M.S.; Fogelström, L.; Malmström, E.; Gedde, U.W.
Abstract: Polyethylene composites based on metal oxide nanoparticles are emerging materials for use in the insulation of extruded HVDC cables. The short-term electrical performance of these materials is adequate, but their stability for extended service needs to be assessed. This study is focussed on the capacity of the nanoparticles to adsorb polar species (water, dicumyl peroxide and byproducts from peroxide-vulcanisation, acetophenone and cumyl alcohol) that have an impact on the electrical conductivity of nanocomposites, the oxidative stability by adsorption of phenolic antioxidants on the nanoparticles and the potential transfer of catalytic impurities from the nanoparticles to the polymer. The adsorption of water, dicumyl peroxide, acetophenone, cumyl alcohol and Irganox 1076 (phenolic antioxidant) on pristine and coated (hydrophobic silanes and poly(lauryl methacrylate)) Al2 O3, MgO and ZnO particles ranging from 25 nm to 2 μm was assessed. Composites based on low-density polyethylene and the particles mentioned (≤12 wt.%) were prepared, the degree of adsorption of Irganox 1076 onto the particles was assessed by OIT measurements, and the release of volatile species at elevated temperature was assessed by TG. The concentration of moisture adsorbed on the particles at 25 °C increased linearly with both increasing hydroxyl group concentration on the particle surfaces and increasing relative humidity. Dicumyl peroxide showed no adsorption on any of the nanoparticles. Acetophenone and cumyl alcohol showed a linear increase in adsorption with increasing concentration of hydroxyl groups, but the quantities were much smaller than those of water. Irganox 1076 adsorbed only onto the uncoated nanoparticles. Uncoated ZnO nanoparticles that contained ionic species promoted radical formation and a lowering of the OIT. This study showed that carefully coated pure metal oxide nanoparticles are not likely to adsorb phenolic antioxidants or dicumyl peroxide, but that they have the capacity to adsorb moisture and polar byproducts from peroxide vulcanisation, and that they will not introduce destabilizing ionic species into the polymer matrix. Low contents of dry, equiaxed ZnO and MgO particles strongly retarded the release of volatile species at temperatures above 300 °C.